A Simulation Study on Adaptive Assignment Versus Randomizations in Clinical Trials - Chien-Tai Lin; Yun-Wei Li; Yi-Jun Hong (Mathematics)
This study investigates a sequential clinical trial comparing two treatments with dichotomous outcomes. We evaluate the effectiveness of five adaptive procedures and three randomization methods for assigning patients to different therapies. The primary objective is to identify an optimal treatment allocation policy that maximizes the proportion of successful outcomes in a trial. By comparing the performance of adaptive and randomized procedures, this research provides valuable insights for enhancing treatment allocation strategies in clinical trials, ultimately aiming to improve the overall success rates of therapeutic interventions.